Incidence of Type 1 diabetes and factors associated with presence and severity of ketoacidosis at onset in children - Tumini, Stefano; Baki, Salwa; Kosteria, Ioanna; Di Giuseppe, Italo; Levantini, Gabriella (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: To assess the incidence of Type 1 Diabetes Mellitus (T1DM) during the period 2012-2017, the frequency and severity of ketoacidosis (DKA) at diabetes onset, and the factors associated with DKA in children and adolescents younger than 18 years old in the Abruzzo region, Italy. Methods: All incident cases of T1DM (0-17 years old) diagnosed between January 2012 and December 2017 were included. Data about the patients were obtained from two independent sources; insulin prescriptions and medical records. Clinical data at diabetes onset, as well as demographic and non-demographic data, including center of first hospitalization, distance to regional reference center and number of pediatricians (per 1000 residents younger than 18 years) were collected and evaluated. Results: During 2012-2017 period, 177 patients were diagnosed with T1DM. In 2012, T1DM incidence was 15.6 per 100,000/year; in 2013, 16.4 per 100,000/year; in 2014, 11.6 per 100,000/year; in 2015, 14.2 per 100,000/year; in 2016, 16.2 per 100,000/year and in 2017, 12.2 per 100,000/year. DKA was present in 29.3% of patients, 6.9% with severe DKA. The DKA presence was correlated to age (p<0.02), ethnicity (p<0.04), being transferred to a specialist center instead of being directly admitted to one (p<0.002) and the number of pediatricians in the population (p<0.01). The DKA severity was associated with the delay of transfer (p<0.04). Conclusions: Being admitted directly to a specialist center is very important and it could be expression of high alertness of pediatricians. Availability of well-trained pediatricians is necessary for the prevention of DKA. (www.actabiomedica.it)